A capacidade postulatória como uma situação jurídica processual simples: ensaio em defesa de uma teoria das capacidades em direito - Gouveia Filho, Roberto Pinheiro Campos (2008)
The general theory of Law is an universal legal science, which studies the fundamental legal concepts. This theory helps to find the main premise of this dissertation: the concept of legal situation. This legal situation permits divisions. One of those is relevant to us: the simple legal situations. The most important of it the legal capacity is the generic suitability given by the legal planning for a fact person to name some legal situation and, this way, be character of Law. All the existing capacities in the legal scenario, comes from a matrix capacity (legal) and are useful to the Law s valid practice. Given this notion, it s possible to make a theory of the Law s capacities: this is the second main premise of this essay. The procedural Law, like a legal extension, could not be out of the reach of the general theory of Law. So, all that was reasoned before is applicable: this is the minor premise of this essay. In the procedural relation, some simple legal situation, for example: the postulator capacity (ability to the procedural characters to practice validly some acts of the lawsuit). After writing this brief, it is possible to affirm that the objective of the essay is to study the formals aspects and concepts of the postulator capacity, characterizing in a theory of Law s capacity, using the notion of the legal situation given by the general theory of Law